(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
Abstract: Vocational or technical education is inseparable from the application and advancement of technology, particularly the Internet of Things (IoT), which has brought significant changes to various fields, including vocational education at the Faculty of Engineering, Universitas Negeri Makassar (FT UNM). Vocational education students require interactive learning media to facilitate their understanding of microcontroller fundamentals and IoT applications. The main issue addressed in this study is the absence of learning media based on microcontrollers and IoT applications. This study aims to develop an IoT-based microcontroller trainer media using three main types of microcontrollers: (1) ATmega, (2) Arduino Uno, and (3) NodeMCU. The trainer media is designed to enable students to learn programming steps, hardware integration, and IoT connectivity within a unified platform. The development method employed is Research and Development (R&D), encompassing stages from needs analysis to evaluation. Testing with students revealed that the trainer media effectively enhanced their understanding of microcontrollers and IoT. The implementation and trial results showed that 85% of students could utilize the product and practically and interactively analyze basic IoT concepts. This study demonstrates that the developed trainer media serves as an essential learning tool to support vocational education for students in Electronic Engineering Education.